FEASIBILITY TEST ANALYSIS OF PLANETARY TYPE STARTER MOTOR E-MODULE FOR VOCATIONAL HIGH SCHOOL LEARNING - Priananda, Anung; Hadromi, Hadromi (Journal of Research and Educational Research Evaluation, 2020)
The purpose of this study is to develop and test the feasibility of e-modules, analyze the learning outcomes of learners after using e-modules, and know the response of learners to e-modules. Feasibility testing is reviewed from 1) Media feasibility, 2) Material feasibility, and 3) Student learning achievement. The research started from the development of e-modules with ADDIE development model which is then conducted feasibility testing of e-modules, learning homework, and student response in using e-modules. Based on the results of the calculation of learning media feasibility test obtained a percentage of 90% for media experts and 84.17% for material experts, including in the category of very feasible. The calculation of the feasibility of student learning outcomes was done with t-test which is tcount = 13.73 > ttable = 2.04. The increase in student learning outcomes obtained an average test gain of 0.64 with a moderate increase category. Analysis of students' responses to learning media obtained a percentage of 90.61% so that the learning media developed falls into the category of very practical and feasible to apply.